Treatment of Systemic Inflammation with Itolizumab: A Single Center Experience - Filgueira, Lazaro M; Caballero, Armando; Betancourt, Julio; Hidalgo, Carlos; Sanchez, Naivy; Senrra, Ariam; González, Delvis; Aguilera, Yaumara; Lorenzo, Geidy; Cepeda, Meylán; et al. (Archives of Clinical and Medical Case Reports, 2022)
A hypercytokinemia ending in pulmonary and systemic illness occurs in severe COVID-19 patients. Mature T lymphocytes express CD6, a molecule that regulates antigen specific responses of T cells. Itolizumab is an anti-CD6 antibody, which inhibits the proliferation of naïve T-cells and reduces the secretion of pro-inflammatory cytokines. The objective of this study was to preliminary assess the safety and impact of itolizumab on interleukin 6, seroconversion and clinical outcome of 40 COVID-19 patients treated at the Manuel Fajardo Hospital in Santa Clara, Cuba. Itolizumab was used in combination with other drugs as part of an expanded access trial. The protocol was registered in the Cuban Registry for Trials (http://rpcec.sld.cu/trials/RPCEC00000311-En) in April 2020. Median age was 78.5 and almost all subjects had at least one condition predisposing to higher mortality. Thirteen patients received a single infusion, 24 received 2 doses and 3 patients needed 3 itolizumab infusions. Time from hospital admission to trial entry was 13, 5 and 1 day for critical, severe and moderate patients. The antibody was safe and did not increase lymphopenia. Post-itolizumab secondary infections were only seen in patients with lengthy ICU stay. Interleukin-6 decreased in critical patients with high concentration and did not augment in moderate and severe individuals. IgG seropositivity against the SARS-CoV-2 nucleocapside peptides increased on time. In spite of their poor prognosis, 29 out of 40 patients (72.5%) successfully recovered. Although this was not a randomized study, preliminary data suggest that itolizumab reduced the death probability in comparison to observed matched controls.